Management Considerations for Wheat Production in Florida - David L. Wright; Ann R. Blount; Ron D. Barnett; Cheryl L. Mackowiak; Nicholas Dufault; James Marois (EDIS, 2013)
Higher wheat prices created the impetus for growing wheat in the southeastern United States. Since increasing amounts of corn have been diverted to ethanol production, there is a shortage of grain for America’s livestock industry. This shortage results in higher wheat and soybean prices. Wheat and soybean have been grown together as a double crop throughout the Southeast for many years, which generally increases profitability compared with growing only one of the crops. Planting wheat followed by cotton, peanut or grain sorghum has also become a common practice. The best management practices for high yields of wheat in the Southeast Coastal Plain are well established. This 3-page fact sheet lists production practices for small grains in Florida. Written by D.L. Wright, A.R. Blount, R.D. Barnett, C.L. Mackowiak, N. Dufault, and J. Marois, and published by the UF Department of Agronomy, October 2013.